Insertional assembly of actin filament barbed ends in association with formins produces piconewton forces - Kovar, David R. (National Academy of Sciences, 2004)
Formins are large multidomain proteins required for assembly of actin cables that contribute to the polarity and division of animal and fungal cells. Formin homology-1 (FH1) domains bind profilin, and highly conserved FH2 domains nucleate actin filaments. We characterized the effects of two formins, budding yeast Bni1p and fission yeast Cdc12p, on actin assembly. We used evanescent wave fluorescence microscopy to observe assembly of actin filaments (i) nucleated by soluble formin FH1FH2 domains and (ii) associated with formin FH1FH2 domains immobilized on microscope slides. Bni1p(FH1FH2)p and Cdc12p(FH1FH2)p nucleated new actin filaments or captured the barbed ends of preformed actin filaments that grew by insertion of subunits between the immobilized formin and the barbed end of the filament. Both formins remained bound to growing actin filament barbed ends for >1,000 sec. Elongation of a filament between an immobilized formin and a second anchor point buckled filament segments as short as 0.7 μm, demonstrating that polymerization of single actin filaments produces forces of >1 piconewton, close to the theoretical maximum. After buckling, further growth produced long loops that did not supercoil, suggesting that formins do not stair step along the two subunits exposed on the growing barbed end. In agreement, Arp2/3 complex branched filaments did not rotate as they grew from formins attached to the slide surface. Formins are not mechanistically identical because barbed end elongation from Cdc12(FH1FH2)p, but not Bni1(FH1FH2)p, requires profilin. However, profilin increased the rate of Bni1(FH1FH2)p-mediated barbed end elongation from 75% to 100% of full-speed.